Liver Tumors Epidemiology, Diagnosis, Prevention and Treatment - Reeves, Helen; Manas, Derek M.; Lochan, Rajiv (IntechOpen, 2013)
The prognosis for individuals with liver cancer is frequently poor. Cancers include those which have metastasized to the liver from elsewhere, reflecting advanced stage disease where cure is rarely possible. Similarly, primary liver cancer frequently complicates chronic liver disease, which further limits therapeutic options. Despite these dismal facts, there are signs that change is imminent. Not only have imaging modalities and surgical techniques improved, but preventive strategies and medical therapies show promise. The topic of liver tumors is comprehensively reviewed in this book, with a focus on recent developments relevant to both researchers and clinicians.